LIFE AFTER NATURAL DISASTER: THE CASE OF RESETTLEMENT POLICY IN PAGERJURANG, YOGYAKARTA - M. Rizki Pratama; Abd. Qadir Muslim; Bayu Amengku Praja; Bayu Indra Pratama; Endry Putra (Universitas Halu Oleo, 2020)
Public policy in managing natural disasters in Indonesia has not yet optimal. Nonetheless, there emerge programs to deal with natural disasters as the case of the 2010 Mount Merapi eruption. The government relocated the survivors using the Rekompak (Community-Based Rehabilitation and Reconstruction of Society and Settlement) program. Researcher employs interpretative approaches to understanding the reality which experienced by local inhabitants. Rekompak finished in 2014 at Pagerjurang, but this study uncover the side of the survivors who have moved to the new residential area. As the final statement, this study presents that moving residents' residences is not only a matter of physical displacement, but other conditions might hinder the resilience of local inhabitants such as changes in economic and socio-cultural conditions.